Synthesis, growth process and photoluminescence properties of SrWO4 powders - Sczancoski, J. C.; Cavalcante, L. S.; Joya, M. R.; Espinosa, J. W. M. [UNESP]; Pizani, P. S.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Academic Press Inc. Elsevier B.V., 2009)
SrWO4 powders were synthesized by the co-precipitation method and processed in a microwave-hydrothermal (MH) at 140 degrees C for different times. The obtained powders were analyzed by X-ray diffraction (XRD), micro-Raman (MR) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, field-emission gun scanning electron microscopy (FEG-SEM), Ultraviolet-visible (UV-vis) absorption spectroscopy anti photoluminescence (PL) measurements. XRD patterns and MR spectra showed that the SrWO4 powders present a scheelite-type tetragonal structure without the presence of deleterious phases. Fr-IR spectra exhibited a high absorption band situated at 831.57 cm(-1), which was ascribed to the W-O antisymmetric stretching vibrations into the [WO4] tetrahedron groups. FEG-SEM micrographs suggested that the processing time is able to influence in the growth process and morphology of SrWO4 powders. UV-vis absorption spectra revealed different optical band gap values for these powders. A green PL emission at room temperature was verified in SrWO4 powders when excited with 488 nm wavelength. (C) 2008 Elsevier Ins. All rights reserved.
Keywords: SrWO4; Microwave; Growth process; Band gap; Photoluminescence